2021
DOI: 10.1002/aur.2587
|View full text |Cite
|
Sign up to set email alerts
|

Muscle strength and executive function in children and adolescents with autism spectrum disorder

Abstract: The development of effective (non-pharmacological) treatment approaches for executive dysfunction in autism spectrum disorder (ASD) requires evidence that factors influencing this domain can be modified by behavioral interventions. The present cross-sectional study investigated the relative associations of ASD, muscle strength and body mass index with executive function and information processing among the Healthy Brain Network cohort. Patients with ASD (N = 174) and healthy peers (N = 202) aged 5 to 18 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Studies have shown that among various factors leading to death, death due to reduced physical fitness and reduced exercise time has become the fourth most prevalent [ 22 ]. Research also shows that people with higher muscle strength have improved psychological symptoms, and the two are positively correlated [ 23 , 24 ]. A survey conducted by Tao et al [ 25 ] of 5453 middle school students in China showed that low- to moderate-intensity physical activity was a protective factor for depression in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that among various factors leading to death, death due to reduced physical fitness and reduced exercise time has become the fourth most prevalent [ 22 ]. Research also shows that people with higher muscle strength have improved psychological symptoms, and the two are positively correlated [ 23 , 24 ]. A survey conducted by Tao et al [ 25 ] of 5453 middle school students in China showed that low- to moderate-intensity physical activity was a protective factor for depression in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between motor performance and movement quality is closely related to the severity level of the disorder [ 67 , 68 ]. Moreover, motor [ 35 , 37 , 43 ], sensory [ 69 ], cognitive [ 46 ], and socio-communicative skills impairments [ 45 , 70 , 71 , 72 ] impact the development of their occupations, including activities of daily living, learning, leisure, and social participation in their communities [ 73 , 74 ]. If this program is effective, it should be implemented in schools, clinics, and associations specialising in the education and treatment of ASD individuals because it is an innovative and easy-to-apply program, resulting in a tool for the improvement of the aforementioned skills and the inclusion of these children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…[ 44 ]. Therefore, it seems important to provide children with autism with opportunities for movement to enhance their motor, cognitive, and social development [ 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…The physical fitness of children and adolescents mainly includes cardiorespiratory fitness, muscle strength, speed quality and flexibility. In the past, studies on the physical fitness of children and adolescents often used a certain physical fitness project for research, which could not fully reflect the physical fitness level of children and adolescents, so there were certain limitations [ 5 , 6 , 7 ]. For example, a study analyzed the relationship between cardiorespiratory fitness and waist circumference in Chinese children and adolescents; cardiorespiratory fitness was measured by 20 m shuttle run test, and the analysis showed that the relationship between cardiorespiratory fitness and waist circumference showed an inverted “U” curve [ 8 ].…”
Section: Introductionmentioning
confidence: 99%